Biology of rhomboid proteases in infectious diseases. (December 2016) - Dogga, Sunil Kumar; Soldati-Favre, Dominique
Abstract: Rhomboids are a well-conserved class of intramembrane serine proteases found in all kingdoms of life, sharing a conserved core structure of at least six transmembrane (TM) domains that contain the catalytic serine-histidine dyad. The rhomboid proteases, which cleave membrane embedded substrates within their TM domains, are emerging as an important group of enzymes controlling a myriad of biological processes. These enzymes are found in a wide variety of pathogens manifesting important roles in their pathological processes. Accordingly, they have received considerable attention as potential targets for pharmacological intervention over the past few years. This review provides a general update on rhomboid proteases and their roles in pathogenesis of human infectious agents.